Pulmonary cryptococcosis due to Cryptococcus gattii in an immunocompetent patient: A case report (Research, Society and Development, 2024)
Introduction: Cryptococcosis is a fungal infection that can affect humans, primarily causing infections in the central nervous system and lungs. Cryptococcus gattii is more prevalent in immunocompetent hosts, with pulmonary infections. Objective: To describe the case of an immunocompetent patient with pneumonia caused by Cryptococcus gattii. Methods: Data collection through a review of the medical records of a patient admitted to the Hospital Maria Aparecida Pedrossian, Campo Grande, Mato Grosso do Sul. Results: A case is reported of a 55-year-old male, immunocompetent patient, presenting with extensive pulmonary infection due to cryptococcosis, in which Cryptococcus gattii was isolated from a lung biopsy, sputum, and serology. The outcome was unfavorable despite multiple treatment attempts. Conclusion: In patients with pulmonary infection, fungal infections should be considered as a diagnostic possibility, depending on the patient, signs, and symptoms, even though they are less common than bacterial infections. Delayed diagnosis can lead to unfavorable outcomes. Therefore, studies and case reports are necessary to optimize diagnosis and treatment.